PROGRAM PENINGKATAN GIZI BALITA MELALUI PENYULUHAN KADARZI SERTA PENGEMBANGAN PRODUK PANGAN ALTERNATIF BIMA-X DI DESA KRAMATINGGIL KABUPATEN GRESIK - Dwi Faqihatus Syarifah Has; Eka Srirahayu Ariestiningsih (ACADEMICS IN ACTION Journal of Community Empowerment, 2020)
This Community Service Activities will strive to solve the problems of Toddler Nutrition and create a Healthy Village. In this program, the community is expected to be able to improve their toddler's nutritional status, by utilizing the potential of local food so that they can become nutritious and economically valuable alternative food products through an empowerment approach. Empowerment is carried out by providing training to Posyandu cadres and women's organization mothers administrators of Kramatinggil Village, Gresik Regency. The training was carried out in several stages, namely: (1) Counseling on “Kadarzi” and Toddler Nutrition, (2) Counseling on the development of alternative products sourced from local food potential, namely Moringa Leaves and PMT Biscuits, (3) Training on making BIMA-X (PMT Biscuits and Moringa Oleifera Extract), 4) Toddler Nutrition Counseling and Anthropometric Measurement. The use of PMT Biscuits and Moringa Leaves are expected to improve the nutritional status of the community especially toddlers because in the PMT Biscuits and Moringa Leaves there are many Nutrient contents both Macro and Micro products BIMA-X can be presented in four variations preparations, namely: Stick Moringa, Ice Cream, nuggets, and pudding. The methods used are lectures, discussions, product processing training, and counseling. The outputs of this activity are: (1) Understanding of Posyandu Cadres and women's organization mothers administrators regarding Nutrition in Toddlers, (2) Understanding of alternative food products originating from local food potentials and nutritional content, (3) Posyandu Cadre Ability and the management women's organization mothers processes BIMA-X food products, (4) Recognizes the health and nutrition problems faced by toddlers and gets solutions from Nutritionists. To improve the nutritional status of families, especially toddlers, in this dedication activity, Nutritionist Cadres also nominalization Posyandu cadres so that it is expected that Kramatinggil Village, Gresik Regency can become a Healthy Village.Key Words: Counseling “Kadarzi”, Local Food Product Development, BIMA-X, Improved Nutritional Status